Characteristics and outcomes of patients with chronic thromboembolic pulmonary hypertension in the era of modern therapeutic approaches: data from the Polish multicenter registry (BNP-PL) - Grzegorz Kopeć; Olga Dzikowska-Diduch; Ewa Mroczek; Tatiana Mularek-Kubzdela; Łukasz Chrzanowski; Ilona Skoczylas; Michał Tomaszewski; Małgorzata Peregud-Pogorzelska; Danuta Karasek; Ewa Lewicka; Wojciech Jacheć; Zbigniew Gąsior; et al. (SAGE Publishing, 2021)
Background: Significant achievements in the treatment of chronic thromboembolic pulmonary hypertension (CTEPH) have provided effective therapeutic options for most patients. However, the true impact of the changed landscape of CTEPH therapies on patients' management and outcomes is poorly known. We aimed to characterize the incidence, clinical characteristics, and outcomes of CTEPH patients in the modern era of CTEPH therapies. Methods: We analyzed the data of CTEPH adults enrolled in the prospective multicenter registry. Results: We enrolled 516 patients aged 63.8 ± 15.4 years. The incidence rate of CTEPH was 3.96 per million adults per year. The group was burdened with several comorbidities. New oral anticoagulants ( n  = 301; 58.3%) were preferred over vitamin K antagonists ( n  = 159; 30.8%). Pulmonary endarterectomy (PEA) was performed in 120 (23.3%) patients and balloon pulmonary angioplasty (BPA) in 258 (50%) patients. PEA was pretreated with targeted pharmacotherapy in 19 (15.8%) patients, and BPA in 124 (48.1%) patients. Persistent CTEPH was present in 46% of PEA patients and in 65% of patients after completion of BPA. Persistent CTEPH after PEA was treated with targeted pharmacotherapy in 72% and with BPA in 27.7% of patients. At a mean time period of 14.3 ± 5.8 months, 26 patients had died. The use of PEA or BPA was associated with better survival than the use of solely medical treatment. Conclusions: The modern population of CTEPH patients comprises mostly elderly people significantly burdened with comorbid conditions. This calls for treatment decisions that are tailored individually for every patient. The combination of two or three methods is currently a frequent approach in the treatment of CTEPH. Clinical Trial Registration: clinicaltrials.gov/ct2/show/NCT03959748